2010
DOI: 10.1111/j.1601-183x.2010.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma BDNF concentration, Val66Met genetic variant and depression‐related personality traits

Abstract: Brain-derived neurotrophic factor (BDNF) regulates synaptic plasticity and neurogenesis, and BDNF plasma and serum levels have been associated with depression, Alzheimer's disease, and other psychiatric and neurodegenerative disorders. In a relatively large community sample, drawn from the Baltimore Longitudinal Study of Aging (BLSA), we examine whether BDNF plasma concentration is associated with the Val66Met functional polymorphism of the BDNF gene (n = 335) and with depression-related personality traits ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 69 publications
8
41
3
2
Order By: Relevance
“…Of importance, for serum BDNF levels no diurnal variation could be observed for both sexes. These findings might explain the contradictory results (BDNF correlates positively with neuroticism) reported by Terracciano et al [67] in relation to plasma BDNF, although Yasui-Furukori et al [64] recently reported the often observed inverse association between the more unreliable plasma BDNF and harm avoidance in their Japanese sample. Besides this, numbers from Terracciano et al [63] show that plasma and serum BDNF levels only have moderate correlations ( = 0.21, < 0.001).…”
Section: Linking Bdnf Levels To Personality Traitscontrasting
confidence: 51%
See 1 more Smart Citation
“…Of importance, for serum BDNF levels no diurnal variation could be observed for both sexes. These findings might explain the contradictory results (BDNF correlates positively with neuroticism) reported by Terracciano et al [67] in relation to plasma BDNF, although Yasui-Furukori et al [64] recently reported the often observed inverse association between the more unreliable plasma BDNF and harm avoidance in their Japanese sample. Besides this, numbers from Terracciano et al [63] show that plasma and serum BDNF levels only have moderate correlations ( = 0.21, < 0.001).…”
Section: Linking Bdnf Levels To Personality Traitscontrasting
confidence: 51%
“…One earlier study by Terracciano et al [67] even reported a positive association between plasma BDNF levels and two facets of neuroticism. The detailed results of these studies are presented in Table 1.…”
Section: Linking Bdnf Levels To Personality Traitsmentioning
confidence: 99%
“…The Val to Met variant at amino acid 66 (Val66Met) results from a G758A polymorphism (rs6265) in BDNF's 11th exon. The Met allele has been associated with lower serum BDNF (Ozan et al, 2010), though this has not been consistently replicated (Duncan et al, 2009;Terracciano et al, 2010;Zhou et al, 2011). The Met allele has also been associated with increased suicide risk (Kanellopoulos et al, 2011;Pregelj et al, 2011;Sarchiapone et al, 2008), various depression-related traits (Beevers et al, 2009;Gatt et al, 2008;Gatt et al, 2010;Hayden et al, 2010;Jiang et al, 2005;Lau et al, 2010;Montag et al, 2010;Montag et al, 2008;Montag et al, 2009), and occasionally, a depression diagnosis (Aguilera et al, 2009;Borroni et al, 2009;Kim et al, 2008;Lavebratt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, половой диморфизм в отношении черт тревожного ряда наблюдался в зависимости от уровня нейротрофического фактора голов-ного мозга (BDNF): уровень белка в плазме крови прямо коррелировал с чертами тревожного ряда (нейротизмом) и обратно коррелировал с добро-совестностью и экстраверсией у мужчин, но не у женщин (Terracciano et al, 2010a).…”
Section: половые различия в чертах личностиunclassified
“…Молекулярно-генетические исследова-ния выявили ассоциацию данного полиморфного локуса с чертами тре-вожного ряда (Lang et al, 2005) и «добросовестностью» (Hiio et al, 2011). Однако результаты недавно проведенного метаанализа (N = 15 251) не подтвердили достоверную ассоциацию Val66Met с вариацией в чертах тревожного ряда, хотя свидетельствовали об его ассоциации с «экстравер-сией» (Terracciano et al, 2010a).…”
Section: гены системы нейротрофического фактораunclassified